Corrugated cardboard adhesive

Sodium trimetaphosphate replaces borax in corrugated board adhesives, addressing environmental concerns by maintaining adhesive performance and viscosity, thus providing a sustainable alternative for bonding core and liner papers.

JP7610287B2Active Publication Date: 2025-01-08RINOKU CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023034546
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-03-07
Publication Date
2025-01-08
Estimated Expiration
2043-03-07

AI Technical Summary

Technical Problem

Boron compounds like borax, used in conventional corrugated board adhesives, are harmful to human health and the ecosystem, necessitating the development of environmentally friendly alternatives without compromising adhesive performance.

Method used

The use of sodium trimetaphosphate as a crosslinking agent in corrugated board adhesives, replacing borax, by incorporating it into the manufacturing process of both the stain-hole and non-carrier methods, ensuring similar adhesive properties and viscosity profiles.

Benefits of technology

This approach reduces environmental impact while maintaining or improving adhesive strength and viscosity, making it suitable for bonding core and liner papers in corrugated boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610287000005
    Figure 0007610287000005
  • Figure 0007610287000006
    Figure 0007610287000006
  • Figure 0007610287000007
    Figure 0007610287000007
Patent Text Reader

Abstract

To provide an adhesive for corrugated cardboard that is free of borax.SOLUTION: An adhesive for corrugated cardboard is used for bonding core paper and liner paper together. In the production by a non-carrier system, the adhesive for corrugated cardboard comprises the main part, water, starch, caustic soda and sodium trimetaphosphate, and amidosulfuric acid, wherein the mass of the sodium trimetaphosphate is 0.01-0.22 mass% relative to the total mass of the main part, the alkali part and the neutralizer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a corrugating adhesive and a method for making a corrugating adhesive. [Background technology]

[0002] Conventionally, corrugated cardboard glue is made by mixing water, starch, caustic soda, and borax. The quality of the resulting glue depends on the mixing ratio, mixing timing, mixing temperature, and the quality of the starch used, and this affects the productivity of corrugated cardboard production.

[0003] The role of borax is to increase the apparent molecular weight by undergoing a pseudo-crosslinking reaction with starch in the presence of caustic soda. As a result, it increases the adhesive strength and improves initial adhesion. The crosslinking reaction with borax creates intermolecular bonds between starch molecules, which can provide resistance to heat, physical damage, and shear. In addition, the presence of borax increases the water retention of the paste liquid through the crosslinking reaction, and also increases the gel strength. By using an appropriate amount of borax, it can crosslink with starch, increasing gel strength and ultimately improving water retention during adhesion. Using too much borax can cause burrs. Borax improves initial adhesion and can be gelatinized and solidified in a short time.

[0004] With penetration adhesion, the glue penetrates into the paper layers from the surface of the liner and core, filling the gaps between the intertwined fibers and forming a strong bond.Interface adhesion is due to intermolecular forces, forming an adhesive shoulder at the interface between the surface of the liner and core and the adhesive.Cohesive adhesion is when the adhesive that has penetrated the base paper and the shoulder bonding components of the interfacial adhesion form a single group, and the intermolecular bonds of the starch itself join together to form the bond. When gluing the shingle side, since there is no penetrating adhesive, the glue gel strength of this interface adhesive, i.e. the dam of solidification strength, is important. With glue that uses borax, the gel strength is stronger and the glue dam is stronger, making it easier to retain moisture inside and improving water retention. Gel strength can be adjusted. A Brabender chart shows that the use of borax results in a higher peak viscosity upon heating, and an even higher viscosity upon cooling.

[0005] Boron compounds are recognized as chemical substances that may be harmful to human health and ecosystems under the PRTR Law, which was revised in April 2001, and businesses are obligated to report the amount of boron compounds discharged into the environment and transferred in waste to government authorities. The purpose of the PRTR Law is to reduce risks to the environment, and in recent years, interest in environmental conservation has increased with the SDGs and other initiatives, and there is a desire to not use chemical substances that pose environmental risks or to reduce their use. However, there is still no decisive substitute for existing starch paste, taking into account productivity and stable supply.

[0006] Conventionally, methods for producing glue for corrugated cardboard include the stain hole method and the no-carrier method.

[0007] In the Steinhall method, in the carrier section, carrier starch is dispersed in water and caustic soda is added, and in the main section, main water is added, main starch is added, and then borax is added. The conventional Steinhall method uses borax.

[0008] In the no-carrier method, starch is added to water, followed by caustic soda and boric acid, which undergo a neutralization reaction to produce borax. In the conventional no-carrier method, boric acid is used, which produces borax.

[0009] Adhesives for corrugated cardboard are known, for example, as described in Patent Document 1 and Patent Document 2. The adhesive composition for bonding the core paper and the liner paper according to Patent Document 1 comprises one or more crosslinking agents selected from the group consisting of trimetaphosphate, adipic anhydride, phosphoric anhydride, phosphorus oxychloride, acrolein, epichlorohydrin, glyoxal, and melamine, and ungelatinized starch.

[0010] The method for producing a corrugated cardboard adhesive according to Patent Document 2 is a method for producing a corrugated cardboard adhesive for bonding a core paper and a liner paper, and includes the following steps: a first step of adding carrier starch and borax to carrier water and then adding caustic soda, a second step of adding main water, a third step of adding main starch, a fourth step of adding secondary caustic soda, and a fifth step of adding boric acid. However, corrugated cardboard adhesives that do not use borax and are produced by conventional methods for producing corrugated cardboard adhesives are almost unknown. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] JP 2017-95674 A [Patent Document 2] JP 2022-90887 A Summary of the Invention [Problem to be solved by the invention]

[0012] Boron compounds such as borax are substances that are recognized as harmful to humans and ecosystems. In fact, the use of borax in food-safe cardboard boxes such as pizza boxes can have a negative impact on health. There is a need for the development of cardboard adhesives that reduce the environmental impact.

[0013] The present invention has been made in view of the above, and an object of the present invention is to provide a corrugated board adhesive that does not use borax. [Means for solving the problem]

[0014] The corrugated cardboard adhesive of the present invention is a corrugated cardboard adhesive for bonding core paper and liner paper, and when produced by the Steinhole method, the carrier part contains water, a crosslinking agent of sodium trimetaphosphate, starch and caustic soda, the main part contains water and starch, and the sodium trimetaphosphate is contained in an amount of 0.01 to 0.22 mass % relative to the total mass of the carrier part and the main part. The corrugated cardboard adhesive of the present invention is a corrugated cardboard adhesive for bonding core paper and liner paper, and when produced by the Steinhole method, the carrier part contains water, starch and caustic soda, the main part contains water, starch and a crosslinking agent of sodium trimetaphosphate, and the sodium trimetaphosphate is contained in an amount of 0.01 to 0.22 mass % relative to the total mass of the carrier part and the main part.

[0015] The corrugated cardboard adhesive of the present invention is an adhesive for bonding core paper and liner paper, and when produced by a no-carrier system, the adhesive contains water, sodium trimetaphosphate and starch in the main part, water and caustic soda in the alkaline part, and amidosulfuric acid in the neutralizing agent, and contains 0.01 to 0.22 mass % of the sodium trimetaphosphate relative to the total mass of the main part, alkaline part and neutralizing agent.

[0016] The corrugated board adhesive of the present invention is produced without using borax, reducing the burden on the environment. [Brief description of the drawings]

[0017] [Figure 1] FIG. 2 is a schematic diagram for explaining the production of the corrugated board adhesive of the first embodiment. [Diagram 2] FIG. 4 is a schematic diagram illustrating the production of a corrugated board adhesive according to a second embodiment. [Diagram 3] 1 is a graph showing the Brabender viscosity and reaction temperature for Example 1-1, Comparative Example 1-1, and Comparative Example 1-3 for producing the corrugated board adhesive of the first embodiment. [Figure 4] 1 is a graph showing the Brabender viscosity and reaction temperature for Examples 1-1, 1-4, 1-5, 1-6, 1-7, and Comparative Example 1-3 used to prepare the cardboard adhesive of the first embodiment. [Diagram 5] Graph showing Brabender viscosity and reaction temperature according to Example 3 and Comparative Example 3 for preparing a corrugated board adhesive. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, a corrugated board adhesive according to an embodiment of the present invention will be described with reference to the drawings.

[0019] (First embodiment) An illustration of the preparation of the first embodiment corrugating adhesive is shown in Figure 1. The first embodiment corrugating adhesive is produced by adding starch, caustic soda, and sodium trimetaphosphate to water. Corrugated cardboard adhesives produced by specific production methods will be described in the respective Examples.

[0020] In the Steinhall method for manufacturing the corrugated cardboard adhesive of the first embodiment, in the carrier section, starch and caustic soda are added to water, and in the main section, starch is added to the main water, and at this time, sodium trimetaphosphate is added to the carrier section or the main section. The glue liquid that becomes the adhesive for cardboard is made by mixing a carrier part and a main part.

[0021] In the Steinhall method for producing the corrugated cardboard adhesive of the first embodiment, the glue making procedure is as follows: in the carrier section, sodium trimetaphosphate, starch and caustic soda are added to water, and in the main section, main water is added and starch is added. Alternatively, in the Steinhall method for producing the corrugated board adhesive of the first embodiment, the glue making procedure is as follows: in the carrier section, starch and caustic soda are added to water, and in the main section, main water is added, and starch and sodium trimetaphosphate are added.

[0022] In the first embodiment, the starch used was corn starch or tapioca starch. Caustic soda was used, but potassium hydroxide, calcium hydroxide, etc. may be used instead of caustic soda.

[0023] In the first embodiment, sodium trimetaphosphate is used in place of the borax used in the Steinhall process for producing corrugated board adhesive.

[0024] (Viscosity measurement) In cardboard manufacturing sites, viscosity is generally controlled using a Ford cup. The measurement method is to fill the cup with glue and measure the time it takes for the liquid level to fall naturally from the upper needle to the lower needle. This time is called the Ford cup viscosity (unit: seconds). An increase or decrease in Ford cup viscosity is called thickening or thinning, respectively.

[0025] The Ford cup viscosity (seconds) and Brookfield viscosity (mPa·s) of the corrugated board adhesive of the first example were measured.

[0026] (Adhesive strength measurement) In the first example, the adhesive strength (N) of the cardboard adhesive was measured at pressure bonding times of 1 second, 2 seconds, 3 seconds, 4 seconds, 5 seconds, and 10 seconds.

[0027] The present invention will be described in more detail below with respect to the first embodiment, with reference to Examples 1-1 to 1-7 shown in Table 1. The scope of the present invention is not limited to the following Examples 1-1 to 1-7.

[0028] [Table 1]

[0029] Table 1 shows the experimental results of the corrugated cardboard adhesive produced by the Steinhall method in the first embodiment in Examples 1-1 to 1-7, and the experimental results of the comparative examples in Comparative Examples 1-1 to 1-3. Comparative Example 1-1 to Comparative Example 1-3 in Table 1 are the experimental results produced by the conventional Steinhall method. Next, Examples 1-1 to 1-7 will be described in detail.

[0030] <Example 1-1> In the carrier section, 6 g of sodium trimetaphosphate, 120 g of cornstarch and 22 g of caustic soda were added to 1450 g of water at 40° C., and in the main section, 1550 g of main water and 880 g of cornstarch were added.

[0031] In Example 1-1, the Ford cup viscosity was 30 seconds and the B-type viscosity was 230 mPa·s. The adhesive viscosity of the adhesive in the first example was almost close to that of the adhesive using borax in Comparative Example 1-1.

[0032] Comparing Example 1-1 and Comparative Example 1-1, when sodium trimetaphosphate was added, the adhesive viscosity obtained was the same as when borax was used.

[0033] In Example 1-1, cornstarch is used to prepare a cardboard adhesive, which is relatively inexpensive and stable in terms of quality and supply.

[0034] <Example 1-2> In the carrier section, 6 g of sodium trimetaphosphate, 100 g of tapioca starch and 22 g of caustic soda were added to 1450 g of water at 40° C., and in the main section, 1550 g of main water and 900 g of tapioca starch were added.

[0035] In Example 1-2, the Ford cup viscosity was 33 seconds and the B-type viscosity was 230 mPa·s. The adhesive of the first example was a corrugated board adhesive with an adhesive viscosity almost close to that of the adhesive using borax in Comparative Example 1-2.

[0036] As shown in Example 1-2, this corrugated adhesive can also be made using tapioca starch in place of corn starch. Tapioca starch can be used in place of cornstarch to provide the same adhesive properties as borax.

[0037] When preparing the adhesive of the first embodiment, any type of starch can be used.

[0038] <Example 1-3> In the carrier section, 120 g of corn starch and 22 g of caustic soda were added to 1450 g of water at 40° C., and in the main section, 1550 g of main water was added, and 880 g of corn starch and 6 g of sodium trimetaphosphate were added.

[0039] In Example 1-3, the Ford cup viscosity was 30 seconds and the B-type viscosity was 230 mPa·s. The adhesive of the first example was a corrugated board adhesive with an adhesive viscosity almost close to that of the adhesive using borax in Comparative Example 1-1.

[0040] Comparing Example 1-3 with Comparative Example 1-1, it can be confirmed that even when sodium trimetaphosphate is added to the main portion, the same adhesive viscosity can be obtained as when borax is used.

[0041] In making the adhesive of the first embodiment, sodium trimetaphosphate can be used in the main portion as well as the carrier portion.

[0042] <Example 1-4> In the carrier section, 3 g of sodium trimetaphosphate, 120 g of cornstarch, and 22 g of caustic soda were added to 1450 g of water at 40° C., and in the main section, 1550 g of main water and 880 g of cornstarch were added.

[0043] In Example 1-4, the Ford cup viscosity was 29 seconds and the B-type viscosity was 220 mPa·s. The adhesive of the first example was a corrugated board adhesive with an adhesive viscosity almost close to that of the adhesive using borax in Comparative Example 1-1.

[0044] <Example 1-5> In the carrier section, 1 g of sodium trimetaphosphate, 120 g of cornstarch, and 22 g of caustic soda were added to 1450 g of water at 40° C., and in the main section, 1550 g of main water and 880 g of cornstarch were added.

[0045] In Example 1-5, the Ford cup viscosity was 29 seconds and the B-type viscosity was 220 mPa·s. The adhesive of the first example was a corrugated board adhesive with an adhesive viscosity almost close to that of the adhesive using borax in Comparative Example 1-1.

[0046] <Examples 1-6> In the carrier section, 0.5 g of sodium trimetaphosphate, 120 g of cornstarch, and 22 g of caustic soda were added to 1450 g of water at 40° C., and in the main section, 1550 g of main water and 880 g of cornstarch were added.

[0047] In Example 1-6, the Ford cup viscosity was 28 seconds and the B-type viscosity was 212 mPa·s. The adhesive of the first example was a corrugated board adhesive with an adhesive viscosity almost close to that of the adhesive using borax in Comparative Example 1-1.

[0048] <Example 1-7> In the carrier section, 9 g of sodium trimetaphosphate, 120 g of cornstarch, and 22 g of caustic soda were added to 1450 g of water at 40° C., and in the main section, 1550 g of main water and 880 g of cornstarch were added.

[0049] In Example 1-7, the Ford cup viscosity was 31 seconds and the B-type viscosity was 235 mPa·s. The adhesive of the first example was a cardboard adhesive with an adhesive viscosity almost similar to that of the adhesive using borax in Comparative Example 1-1.

[0050] Next, according to Examples 1-1, 1-4 to 1-7 and Comparative Example 1-1, the appropriate addition rate of sodium trimetaphosphate was when the trimetaphosphate concentration relative to starch was 0.01 to 0.6%, and the effect was low when the concentration was less than 0.01%.

[0051] The corrugated cardboard adhesive of the first example was found to be suitable when tested under conditions in which the sodium trimetaphosphate concentration, which indicates the mass of sodium trimetaphosphate relative to the total starch amount, was 0.05 to 0.90 mass %. The cardboard adhesive of the first embodiment was found to be suitable when tested under conditions in which the sodium trimetaphosphate ratio, which indicates the mass of sodium trimetaphosphate relative to the total mass of the carrier portion and the main portion, was 0.01 to 0.22 mass%.

[0052] (Brabender viscosity measurement) The Brabender viscosity (unit: BU) of the samples of Example 1-1 of the first embodiment, Comparative Example 1-1, and Comparative Example 1-4 was measured using a Brabender tester. In the Brabender test, a sample of starch dispersed in an aqueous solution is stirred while being heated, and the resistance to the stirring pin is quantified. The graph shows time on the horizontal axis and viscosity on the vertical axis. The gelatinization process can be understood from the graph.

[0053] Brabender amylogram measurement was performed. Brabender Amylogram E type made by Parker Corporation was used. The temperature was raised to 95°C by 3°C per minute, and the temperature was kept for 10 minutes after reaching 95°C. Then, the temperature was cooled to 55°C by 2°C per minute, and the temperature was kept at 55°C for 15 minutes. The measurement feeler was a pin type.

[0054] The Brabender viscosity and reaction temperature of Example 1-1 of the first embodiment, Comparative Example 1-1, and Comparative Example 1-3 are shown in FIG.

[0055] Example 1-1 has similar gelatinization characteristics to Comparative Example 1-1. Comparative Example 1-3, which does not contain borax or sodium trimetaphosphate, has low viscosity both during heating and cooling, which is different from Example 1-1 and Comparative Example 1-1. There is also a correlation with adhesion test data. It is clear that sodium trimetaphosphate can be used as an alternative to borax.

[0056] Example 1-1 was closer to Comparative Example 1-1 in that the viscosity increased during heating and also increased during cooling.

[0057] The Brabender viscosities and reaction temperatures of Example 1-1, Example 1-4, Example 1-5, Example 1-6, Example 1-7 of the first embodiment and Comparative Example 1-3 are shown in FIG.

[0058] In Examples 1-1, 1-4, 1-5, 1-6 and 1-7, the viscosity during heating was higher than that in Comparative Example 1-3, and the viscosity during cooling was also higher.

[0059] In Example 1-1, the viscosity was high during heating and also high during cooling, which was similar to that of Comparative Example 1-1.

[0060] (Adhesive strength) A pin strength measurement test was conducted. The adhesion temperature was 130℃, the load was 1.7kg (5cm x 10 steps), K280 x reinforced 200 x K280, and a Japan TMC ring crush tester ISO12192, JIS P 8126 were used. The test speed was 12.5 ± 2.5 mm / min, the variable speed was about 3 to 80 mm / min, and the compression stroke was 0 to about 170 mm.

[0061] [Table 2]

[0062] Table 2 shows the results of the adhesive strength of Examples 1-1 to 1-7 and Comparative Examples 1-1 to 1-3.

[0063] The adhesive strength (N) of the adhesives of Examples 1-1 to 1-7 and Comparative Examples 1-1 to 1-3 was measured at pressure bonding times of 1, 2, 3, 4, 5 and 10 seconds.

[0064] A first example corrugated adhesive includes a crosslinker of sodium trimetaphosphate, water, starch, and caustic soda.

[0065] The corrugated cardboard adhesive of the first example was found to be suitable when tested under conditions in which the sodium trimetaphosphate ratio, which indicates the mass of sodium trimetaphosphate relative to the total mass, was 0.01 to 0.22 mass %.

[0066] The method for producing a corrugated cardboard adhesive corresponding to claim 1 of the present invention is a method for producing a corrugated cardboard adhesive for bonding a core paper and a liner paper, and when producing by the Steinhall method, in the carrier part, starch, sodium trimetaphosphate and caustic soda are added to water, and in the main part, starch is added to water, and the sodium trimetaphosphate rate, which indicates the mass of sodium trimetaphosphate relative to the total mass of the carrier part and the main part, is 0.01 to 0.22 mass%.

[0067] The method for producing a corrugated cardboard adhesive corresponding to claim 2 of the present invention is a method for producing a corrugated cardboard adhesive for bonding a core paper and a liner paper, and when producing by the Steinhall method, starch and caustic soda are added to water in the carrier part, and starch and sodium trimetaphosphate are added to water in the main part, and the sodium trimetaphosphate ratio, which indicates the mass of sodium trimetaphosphate relative to the total mass of the carrier part and the main part, is 0.01 to 0.22 mass%.

[0068] (Second embodiment) Next, a second embodiment will be described. In the no-carrier method for producing the corrugated board adhesive of the second embodiment, sodium trimetaphosphate and starch are added to water, then water and caustic soda are added, and amidosulfuric acid is further added.

[0069] In the no-carrier method for producing the corrugated board adhesive of the second embodiment, main water, sodium trimetaphosphate and starch are added to the main part, water and caustic soda are added to the alkaline part, and amidosulfuric acid is added to the neutralizing agent.

[0070] In the examples, the starch used was corn starch or tapioca starch. Instead of caustic soda, potassium hydroxide or calcium hydroxide may be used. Instead of amidosulfuric acid, citric acid, hydrochloric acid, acetic acid, sulfuric acid, phosphoric acid, or the like may be used.

[0071] In the no-carrier system for producing a corrugated board adhesive in the second embodiment, amidosulfuric acid and sodium trimetaphosphate are used instead of boric acid, which produces borax as in the conventional no-carrier system.

[0072] (Viscosity measurement) The Ford cup viscosity (sec) and Brookfield viscosity (mPa·s) of the corrugated board adhesive of the second example were measured.

[0073] (Adhesive strength measurement) The adhesive strength (N) of the corrugated cardboard adhesive of the second embodiment was measured at pressure bonding times of 1 second, 2 seconds, 3 seconds, 4 seconds, 5 seconds, and 10 seconds.

[0074] [Table 3]

[0075] Table 3 shows the experimental results of Examples 2-1 to 2-6 and Comparative Examples 2-1 to 2-3 of the corrugated cardboard adhesive of the present invention produced by the no-carrier system in the second embodiment. Comparative Examples 2-1 to 2-3 shown in Table 3 are the experimental results produced using the conventional no-carrier method. Next, Examples 2-1 to 2-6 will be described in detail.

[0076] <Example 2-1> In the main part, 40° C. water, 6 g of sodium trimetaphosphate, and 1000 g of corn starch were added, in the alkaline part, 500 g of room temperature water and 30 g of caustic soda were added, and in the neutralizing agent, 15 g of amidosulfuric acid was added.

[0077] In Example 2-1, the Ford cup viscosity was 30 seconds and the Brookfield viscosity was 930 mPa·s. The adhesive of the second example was a cardboard adhesive with an adhesive viscosity almost similar to that of the adhesive using borax in Comparative Example 2-1.

[0078] From Example 2-1 and Comparative Example 2-1, it was found that even without using boric acid, which produces borax, by adding amidosulfuric acid to the neutralizing agent and using sodium trimetaphosphate, the same level of adhesion was obtained as when borax was used.

[0079] <Example 2-2> Cornstarch has long been used as a paste for corrugated cardboard because it is relatively inexpensive and has stable quality and supply. In Example 2-1, a corrugated cardboard adhesive is prepared using cornstarch.

[0080] In the main part, 40° C. water, 6 g of sodium trimetaphosphate, and 1000 g of tapioca starch were added, in the alkaline part, 500 g of room temperature water and 30 g of caustic soda were added, and in the neutralizing agent, 15 g of amidosulfuric acid was added.

[0081] In Example 2-2, the Ford cup viscosity was 32 seconds and the B-type viscosity was 880 mPa·s. The adhesive of the second example was a corrugated board adhesive with an adhesive viscosity almost close to that of the adhesive using borax in Comparative Example 2-2.

[0082] As shown in Example 2-2, this corrugated adhesive can also be made using tapioca starch instead of corn starch. Tapioca starch can be used in place of cornstarch to provide the same adhesive properties as borax.

[0083] When preparing the adhesive of the second embodiment, any type of starch can be used.

[0084] <Example 2-3> In the main part, 40° C. water, 3 g of sodium trimetaphosphate, and 1000 g of corn starch were added, in the alkaline part, 500 g of room temperature water and 30 g of caustic soda were added, and in the neutralizing agent, 15 g of amidosulfuric acid was added.

[0085] In Example 2-3, the Ford cup viscosity was 30 seconds and the B-type viscosity was 930 mPa·s. The adhesive of the second example was a corrugated board adhesive with an adhesive viscosity almost close to that of the adhesive using borax in Comparative Example 2-1.

[0086] <Example 2-4> In the main part, 40° C. water, 1 g of sodium trimetaphosphate, and 1000 g of corn starch were added, in the alkaline part, 500 g of room temperature water and 30 g of caustic soda were added, and in the neutralizing agent, 15 g of amidosulfuric acid was added.

[0087] In Example 2-4, the Ford cup viscosity was 30 seconds and the B-type viscosity was 920 mPa·s. The adhesive of the second example was a corrugated board adhesive with an adhesive viscosity almost close to that of the adhesive using borax in Comparative Example 2-1.

[0088] The optimum addition rate of sodium trimetaphosphate was when the trimetaphosphate concentration relative to starch was 0.1-0.6%, and the effect was low when the concentration was less than 0.05%.

[0089] <Example 2-5> In the main part, 40° C. water, 0.5 g of sodium trimetaphosphate, and 1000 g of corn starch were added, in the alkaline part, 500 g of room temperature water and 30 g of caustic soda were added, and in the neutralizing agent, 15 g of amidosulfuric acid was added.

[0090] In Example 2-5, the Ford cup viscosity was 29 seconds and the Brookfield viscosity was 890 mPa·s. The adhesive of the second example was a corrugated board adhesive with an adhesive viscosity almost close to that of the adhesive using borax in Comparative Example 2-1.

[0091] <Example 2-6> In the main part, 40° C. water, 9 g of sodium trimetaphosphate, and 1000 g of corn starch were added, in the alkaline part, 500 g of room temperature water and 30 g of caustic soda were added, and in the neutralizing agent, 15 g of amidosulfuric acid was added.

[0092] In Example 2-6, the Ford cup viscosity was 31 seconds and the Brookfield viscosity was 960 mPa·s. The adhesive of the second example was a corrugated board adhesive with an adhesive viscosity almost close to that of the adhesive using borax in Comparative Example 2-1.

[0093] According to Examples 2-1, 2-2 to 2-6, and Comparative Example 2-1, even in the no-carrier method, the optimum addition rate of sodium trimetaphosphate was when the trimetaphosphate concentration relative to starch was 0.01 to 0.6%, and the effect was reduced when the concentration was less than 0.01%.

[0094] In Examples 2-1 to 2-6, amidosulfuric acid (sulfamic acid) was used as the neutralizing agent.

[0095] The corrugated cardboard adhesive of the second example was found to be suitable when tested under conditions in which the sodium trimetaphosphate concentration, which indicates the mass of sodium trimetaphosphate relative to the total starch amount, was 0.05 to 0.90 mass %. The cardboard adhesive of the second embodiment was found to be suitable when tested under conditions in which the sodium trimetaphosphate ratio, which indicates the mass of sodium trimetaphosphate relative to the total mass of the main part, alkali part, and neutralizing agent, was 0.01 to 0.22 mass%.

[0096] [Table 4]

[0097] Table 4 shows the results of the adhesive strength of Examples 2-1 to 2-6 and Comparative Examples 2-1 to 2-3.

[0098] The adhesive strength (N) of the adhesives of Examples 2-1 to 2-6 and Comparative Examples 2-1 to 2-3 was measured at pressure bonding times of 1 second, 2 seconds, 3 seconds, 4 seconds, 5 seconds, and 10 seconds.

[0099] A second example corrugating adhesive includes a cross-linking agent selected from sodium trimetaphosphate and amidosulfuric acid, water, starch, and caustic soda.

[0100] The cardboard adhesive of the second embodiment was found to be suitable when tested under conditions in which the sodium trimetaphosphate ratio, which indicates the mass of sodium trimetaphosphate relative to the total mass of the main part, alkali part, and neutralizing agent, was 0.01 to 0.22 mass%.

[0101] The second example corrugated adhesive contains sodium trimetaphosphate and amidosulfuric acid.

[0102] The method for producing a corrugated cardboard adhesive corresponding to claim 3 of the present invention is a method for producing a corrugated cardboard adhesive for bonding a core paper and a liner paper, and when producing by a no-carrier system, water, sodium trimetaphosphate and starch are added to the main part, water and caustic soda are added to the alkaline part, and amidosulfuric acid is added to the neutralizing agent, and the sodium trimetaphosphate rate, which indicates the mass of sodium trimetaphosphate relative to the total mass of the carrier part and the main part, is 0.01 to 0.22 mass%.

[0103] (Other Examples) FIG. 5 shows the Brabender viscosity and reaction temperature for Example 3 when trimetaphosphoric acid was used and for Comparative Example 3 when trimetaphosphoric acid was not used. The maximum viscosity was 900 BU in Example 3. The maximum viscosity was 620 BU in Comparative Example 3. Comparing the use of trimetaphosphoric acid and the use of no trimetaphosphoric acid, it can be seen that there is a difference in the maximum viscosity during temperature rise.

[0104] It is preferable that the corrugated board adhesive sample is adjusted so that the starch concentration in the total mass is 8 mass % in the Brabender amylogram, and the maximum viscosity upon heating is 700 BU or more. The corrugated board adhesive preferably has a starch concentration of 8% by mass relative to the total mass of the carrier portion and the main portion, and exhibits a maximum viscosity of 700 BU or more upon heating, as measured by Brabender viscosity. The corrugated board adhesive preferably has a starch concentration of 8% by mass relative to the total mass of the main part, alkali part and neutralizing agent, and exhibits a maximum viscosity of 700 BU or more upon heating, as measured by Brabender viscosity.

[0105] In Example 3, the viscosity was higher when the temperature was increased than in Comparative Example 3, and the viscosity was also higher when the temperature was decreased.

[0106] The corrugated board adhesive of the second embodiment contains one or more neutralizing agents selected from the group consisting of citric acid, hydrochloric acid, acetic acid, sulfuric acid, and phosphoric acid in place of amidosulfuric acid.

[0107] The corrugated board adhesive of the first and second embodiments contains one or more alkalis selected from potassium hydroxide and calcium hydroxide instead of caustic soda.

[0108] The corrugated cardboard adhesive of the present invention can also be produced by the method for producing a corrugated cardboard adhesive described in Japanese Patent Publication No. 7202019, using sodium trimetaphosphate instead of borax. This method for producing a cardboard adhesive is for bonding core paper and liner paper, and includes a first step of adding carrier starch and sodium trimetaphosphate to carrier water and adding caustic soda, a second step of adding main water, a third step of adding main starch, a fourth step of adding secondary caustic soda, and a fifth step of adding sodium trimetaphosphate, in which a carrier sodium trimetaphosphate rate indicating the mass of sodium trimetaphosphate relative to the total mass of the carrier part produced in the first step is 0.01 to 0.22 mass%, a carrier rate indicating the weight ratio of starch in the carrier part to the sum of the starch amount in the carrier part and the starch amount in the main part is 3.0 to 20.0 mass%, and in the fourth step, secondary caustic soda with a secondary caustic soda concentration in the range of 5.0 to 30.0 mass% is used.

[0109] As described above, the present invention is not limited to the above-described embodiment, and can be embodied in various forms without departing from the spirit and scope of the present invention.

Claims

1. A borax-free corrugating adhesive for bonding corrugating medium and liner papers, comprising: When manufacturing using the Steinhall method, The carrier part includes water, a crosslinker of sodium trimetaphosphate, starch, and caustic soda; The main part contains water and starch, The adhesive for corrugated board contains the sodium trimetaphosphate in an amount of 0.01 to 0.22 mass % relative to the total mass of the carrier portion and the main portion.

2. A borax-free corrugating adhesive for bonding corrugating medium and liner papers, comprising: When manufacturing using the Steinhall method, The carrier part includes water, starch, and caustic soda; The main part contains water, starch, and a crosslinker of sodium trimetaphosphate, The adhesive for corrugated board contains the sodium trimetaphosphate in an amount of 0.01 to 0.22 mass % relative to the total mass of the carrier portion and the main portion.

3. A borax-free corrugating adhesive for bonding corrugating medium and liner papers, comprising: When manufacturing using the no-carrier method, The main part contains water, sodium trimetaphosphate and starch, the alkaline part contains water and caustic soda, and the neutralizing agent contains amidosulfuric acid. The adhesive for corrugated board contains the sodium trimetaphosphate in an amount of 0.01 to 0.22% by mass relative to the total mass of the main part, the alkali part, and the neutralizing agent.

4. 4. The corrugated board adhesive according to claim 3, further comprising, in place of the amidosulfuric acid, one or more neutralizing agents selected from the group consisting of citric acid, hydrochloric acid, acetic acid, sulfuric acid and phosphoric acid.

5. 2. The corrugated board adhesive according to claim 1, further comprising one or more alkalis selected from potassium hydroxide and calcium hydroxide in place of the caustic soda.

6. 3. The corrugated board adhesive according to claim 2, further comprising one or more alkalis selected from potassium hydroxide and calcium hydroxide in place of the caustic soda.

7. 4. The corrugated board adhesive according to claim 3, further comprising one or more alkalis selected from potassium hydroxide and calcium hydroxide in place of the caustic soda.

Citation Information

Patent Citations

  • Adhesive for corrugated cardboard, not containing boron compound

    JP2007224099A

  • Adhesive for corrugated cardboard

    JP2017095674A

  • Additive for corrugated cardboard

    JP2019163392A

  • Method for manufacturing adhesive for cardboard

    JP2022090887A